Kontroversi Jazbah dan Suluk dalam Tarekat Al-Naqsyabandiyah Al-Khalidiyah - Nur, Faisal Muhammad (Prodi Studi Agama-Agama, 2023)
Jazbah and mysticism are part of the Islamic Shari'a and are also the spirit of the Islamic Shari'a to unite Allah SWT. The spiritual teachings of Jazbah and Sufi mysticism can be used as a solution to overcoming various kinds of problems in human life and can maintain harmony both internally and between religious communities, because the foundation of Sufi is love and compassion (mahabbah). This article belongs to literature research with a qualitative approach. The methodology used is a descriptive analysis study. The reference sources used are literacy references such as books and journals related to religious moderation. The results of the research in essence there is no controversy between fiqh scholars and tasawwuf scholars in the implementation of jazbah and mysticism in the Naqsyabandiyah order because that is one way to achieve the degree of ihsan.ABSTRAKJazbah dan suluk merupakan bagian dari Syariát Islam dan juga merupakan ruh dari Syariát Islam untuk meng-Esakan Allah Swt. Ajaran spiritual Jazbah dan suluk sufi dapat dijadikan sebagai solusi untuk menanggulangi berbagai macam problematika kehidupan manusia serta dapat menjaga kerukunan baik intern maupun antar ummat beragama, karena pondasi dari sufi adalah cinta dan kasih sayang (mahabbah). Artikel ini tergolong dalam penelitian pustaka dengan pendekatan kualitatif. Adapun metodologi yang digunakan adalah studi deskriptif analisis. Sumber rujukan yang digunakan adalah referensi literasi seperti buku dan jurnal terkait. Hasil penelitian pada hakekatnya tidak ada kontroversi antara ulama fiqih dengan ulama tasawuf dalam pelaksanaan jazbah dan suluk dalam tarekat Naqsyabandiyah sebab itu merupakan salah satu jalan untuk mencapai derajat ihsan.